Effects Of Argon Shielding Gas Flow Rate On Welding Quality Of Mild Steel - Zulkipli, Nur Hidayah (2018)
Welding is a method to join two or more parts permanently. Gas Metal Arc Welding (GMAW) also known as Metal Inert Gas (MIG) is one of the process in welding. In GMAW, there are a continuously solid wire electrode that come together with shielding gas. There are several type of shielding gases in welding industry, but the most commonly used are argon, helium, carbon dioxide and oxygen. The function of shielding gas in welding operation is to protect the weld pool from oxidation. Shielding gas types also plays an important role in producing a good quality of welding as each of them have different advantages and disadvantages. There are several studies that have been done to study the effects of shielding gases and their combination on welding quality, but there is lack of study on how flow rate of pure argon gas may affects the quality of the welding. The purpose of this study is to identify the effects of different flow rates of argon gas on welding quality and to suggest the best flow rate of argon gas within the evaluated range. There are three type of welding characterizations in determining the welding quality that have been investigated which are strength, hardness and microstructure of the welded sample. In order to observe and determine the welding characterizations, three tests have been used which are tensile, microhardness and microstructure test respectively. Minitab17 (Analysis of Variance (ANOVA) and boxplot) is the tool that has been used to analyse the data and result of the tests. From the result obtained, the sample welded with 45 SCFH flow rate of argon gas has the highest strength and hardness value compare to the others. As the conclusion, it is suggested that the best flow rate of argon gas within the evaluated range is 45 SCFH. There are some recommendations for a better future study that have been recommended in the last chapter of this report.